Embodiment in a strong virtual body influences weight lifting endurance - Michael-Grigoriou, Despina; Slater, Mel (My University, 2012)
Recent research has shown that appropriate multisensory stimulation can quickly generate the illusion in people that their body has changed in some significant way, for example as shown in the rubber hand illusion (1). Similar multisensory techniques have also been applied to illusory body ownership of a manikin seen from third (2) or first person perspective (3) using video streamed through head-mounted displays, and also of a virtual body experienced in immersive virtual reality (4). However, although the evidence is strong that illusory body ownership occurs, no attention has been paid to the psychological and behavioural consequences of illusory ownership over a body that is quite different from the real body. When someone is immersed in a virtual environment with a body form that is substantially different from their own, do they exhibit concomitant attitudinal or behavioural changes? We addressed this issue by considering the consequences of virtual body ownership on weight lifting endurance time. The virtual body was either very weak or very strong looking. Our aim was to investigate whether body ownership over a very strong or very weak looking virtual body would influence weight lifting endurance time.
Keywords: Body; Virtual body; Virtual reality